The clinical value of computed tomography Hounsfield unit for diagnosing palpable inguinal lymph node metastasis in patients with penile cancer - Li, Yu; Chen, Yu; Xie, Gansheng; Li, Gang; Yin, Huming (Frontiers in Oncology, 2025)
BackgroundComputed tomography (CT) Hounsfield units (HUs) of pathologically confirmed metastatic inguinal lymph nodes (ILNs) were proved to be higher than negative ones. We designed this study to explore the clinical value of CT HU for diagnosing palpable ILN metastasis in patients with penile cancer.MethodsA total of 32 patients with penile cancer, including 84 palpable ILNs, were recruited in this study. They all performed 5-mm layer pelvic contrast-enhanced CT (CE-CT) before treatment. The palpable ILNs were matched with CT image. By using radiologic software PACS, the layer with a maximum cross-sectional area of target lymph node was selected, and the short axis was defined as diameter. We outlined the edge of target lymph nodes, and the software automatically calculated its area, maximum CT HU, and average CT HU. All target ILNs were biopsied by surgery to confirm the presence of metastasis.ResultsCompared with non-metastatic ILNs, metastatic ILNs had larger diameter, area, maximum non-contrast CT (NC-CT) HU, maximum arterial-phase CE-CT (ACE-CT) HU, average NC-CT HU, and average ACE-CT HU, with statistically significant differences (P < 0.05). Receiver operating characteristic analysis showed the all six parameters (maximum NC-CT HU, maximum ACE-CT HU, average NC-CT HU, average ACE-CT HU, diameter, and area) had significant diagnostic value for ILN metastasis, with an area under the curve of 0.847, 0.853, 0.900, 0.919, 0.809, and 0.789, respectively. The average ACE-CT HU (cutoff: 40.5) had the highest accuracy as 0.857, and maximum NC-CT HU (cutoff: 51.5) had the highest sensitivity of 0.897.ConclusionILN CT HU was clinically valuable for the diagnosis of palpable ILN metastasis in patients with newly diagnosed penile cancer.